PENGARUH VARIASI DIAMETER UJUNG NOZZLE TERHADAP LAJU UAP UNTUK MENGGERAKAN TURBIN PLTSa - Daton Trisnadana, I Nyoman; Indra Partha, Cok. Gede; Janardana, I Gusti Ngurah (Program Studi Teknik Elektro UNUD, 2023)
Garbage is a very serious problem in the coastal areas of the beaches in Bali because the management of postal waste from the sea is not optimal. One way of processing waste is using a waste power plant (PLTSa) that can generate electricity. This study aims to find out how the effect of variations in the diameter of the nozzle on the rate of steam generated to drive the PLTSa turbine, with this research method using descriptive quantitative. Tests on the PLTSa prototype used a single-stage impulse turbine using a runner diameter of 44cm and a total of 75 turbine blades. This prototype uses 3 nozzle diameter variations, namely 3mm, 6mm and 9mm with a boiler output steam of 3 bar so that the highest average steam rate occurs at a nozzle diameter of 6mm to get a result of 1470 rpm before connecting the generator and 2460 rpm after connecting the generator.